Tiktok’s Role on Guerilla Marketing in Digital Marketing Era: Case Study on Titktok Account of @sovella.id and @moutfit_id - Jayadi, Peri; Putri, Seprianti Eka (SIMAK, 2023)
This research aims to analyze the role of TikTok in guerilla marketing in the digital marketing era. The type of research used is descriptive qualitative. The primary data used in this research was obtained from observations of phenomena by researchers on the TikTok accounts @sovella.id and @moutfit_id. The research results show that the power of social media, especially TikTok, must be considered in the current digital marketing era. Companies can use this power to market their products. TikTok is a new marketing media platform that many small, medium, and large businesses use. Business people consider that this TikTok-based marketing model generally requires relatively low costs and is more communicative and interactive. The concept of guerilla marketing using platforms such as TikTok is considered satisfactory. Several existing TikTok features, such as TikTok stories, TikTok live, hashtags, and posts in photos and videos, have been verified to support this guerilla marketing. Business people also use the TikTok feature to create accounts for sales and promotions. Apart from that, it is common for business people to give giveaways to followers as part of their marketing strategy.